Klemens Szaniawski - osoba i dzieło - Jedynak, Anna (Filozofia Nauki, 2001)
The author is one of the pupils of Klemens Szaniawski. Szaniawski has lead a very active life as a scientist and a public activist. His public activity is quite well-known. His early period of life and scientific interests are not so well-known, however. And it is these latter matters that the author focuses on in her paper.